Whole-genome and multisector exome sequencing of primary and post-treatment glioblastoma reveals patterns of tumor evolution - Kim, Hoon; Zheng, Siyuan; Amini, Seyed S.; Virk, Selene M.; Mikkelsen, Tom; Brat, Daniel J.; Grimsby, Jonna; Sougnez, Carrie; Muller, Florian; Hu, Jian; Sloan, Andrew E.; Cohen, Mark L.; et al.

(untitled) (Genome Research, 2015)
Glioblastoma (GBM) is a prototypical heterogeneous brain tumor refractory to conventional therapy. A small residual population of cells escapes surgery and chemoradiation, resulting in a typically fatal tumor recurrence ∼7 mo after diagnosis. Understanding the molecular architecture of this residual population is critical for the development of successful therapies. We used whole-genome sequencing and whole-exome sequencing of multiple sectors from primary and paired recurrent GBM tumors to reconstruct the genomic profile of residual, therapy resistant tumor initiating cells. We found that genetic alteration of the p53 pathway is a primary molecular event predictive of a high number of subclonal mutations in glioblastoma. The genomic road leading to recurrence is highly idiosyncratic but can be broadly classified into linear recurrences that share extensive genetic similarity with the primary tumor and can be directly traced to one of its specific sectors, and divergent recurrences that share few genetic alterations with the primary tumor and originate from cells that branched off early during tumorigenesis. Our study provides mechanistic insights into how genetic alterations in primary tumors impact the ensuing evolution of tumor cells and the emergence of subclonal heterogeneity.